Sociability and quality of work life in a flexible work setting. The experience of supermarket workers in Santiago-Chile - Stecher Guzmán, Antonio; Godoy Catalán, Lorena; Toro Cifuentes, Juan Pablo (Revista de Psicología, 2012)
This article presents the results of an investigation on the building of relationships of workers of a large enterprise of supermarkets in Santiago de Chile, as well as the implications of these patterns of sociability in the quality of working life. Twenty workers and three key informants were interviewed. Additionally, a non-participant observation was conducted at a store of the supermarket. The data were analyzed using procedures of qualitative content analysis. The results suggest the existence of a dense network of interpersonal ties of fellowship that are built despite the difficulties posed by flexible forms of organization. These relationships operate as buffers of work demands, are valued by workers and keep a positive relationship with the quality of working life.